Coupled thermal and hydraulic algebraic models for an open self‐ventilated induction machine. Issue 8 (1st September 2015) - Malumbres, Jose Angel; Satrustegui, Marco; Elosegui, Ibon; Martínez‐Iturralde, Miguel
Abstract : The prediction of the thermal behaviour of electric motors in the early stages of their design is a critical factor for reducing time and cost in the design process. In complex machine topologies such as open self‐ventilated machines, there are several phenomenas to take into account in order to predict the correct thermal behaviour of the machine. In this study, a thermal model coupled with a hydraulic model is presented. These models provide information of the thermal behaviour of the machine. First, the complete thermal circuit is described, with some emphasis in the specially modelled parts. Then, the heat transfer coefficients for each surface inside the machine are presented, by the use of dimensionless correlations that avoids the need of previous knowledge. Moreover, the hydraulic model of the machine is studied, and also the coupling methodology between the two models is described for both steady state and transient calculations. Finally, the results from the model are validated using the data from two experimental runs, the first one with constant torque and speed, and the other with variable power, in a standardised service cycle, with a difference in the rotor bars and the stator winding below ±10°C.